Analisis Intervensi Kebijakan Kenaikan Tarif Dasar Listrik (TDL) Tahun 2017 Terhadap Pemakaian Listrik Wilayah SULSELRABAR - Ahmad Zaki; Rahmat Syam; Ahmad Firjatullah Hakim (Journal of Mathematics, Computations and Statistics, 2019)
This research is an implementation research about intervention analysis that modelling time series data effected by the existence of an event or intervention. This research aimed to determine the model of intervention of the step function with time of intervention (T) derived from process of ARIMA preintervensi modelling, identification of response of intervention, intervention parameter estimation and examination diagnosis of intervention model. As for the data that was used in the form of data of the using of electricity (in KWh), the category of households with power of 900 VA, South Southeast West Sulawesi Region (SULSELRABAR) from January, 2016 to December, 2017 were obtained from PT PLN Persero SULSELRABAR Area Of Makassar. Based on the analysis result obtained that there is derivation towards the using of electricity in the month after the intervention, it shows the impact of government policies that raising the electricity base tarif rate (defined as the intervention).